Accelerating editorial processes in scientific journals: Leveraging AI for rapid manuscript review - Luca Fiorillo; Vini Mehta (Oral Oncology Reports)
Introduction: Artificial intelligence (AI) integration in business is increasingly recognized for enhancing productivity and efficiency. AI automates routine tasks and accelerates decision-making processes, optimizing operations and data analysis. This paper discusses the emergence of AI chat assistants in various sectors, focusing on models like GPT-3, Watson Assistant, Dialogflow, Alexa, Siri, Cortana, and Google Bard. These AI chat assistants exemplify the transformative impact of AI technologies in everyday life. Materials and methods: The study explores AI's role in chatbot development, examining how AI algorithms and machine learning facilitate human-like conversations in diverse industries. The method includes a detailed analysis of AI-powered chatbots' customer service, healthcare, and e-commerce applications. The manuscript also introduces an AI-assisted peer review methodology, employing ChatGPT to analyze and comment on scientific manuscripts, aiming to enhance the efficiency and quality of the academic review process. Results: The AI-assisted review of selected manuscripts demonstrates the potential of ChatGPT in providing insightful feedback and suggestions. The study showcases how AI can contribute to improved manuscript quality, increased efficiency in review processes, and enhanced accessibility. The results highlight the importance of addressing ethical considerations, including privacy and bias, in deploying AI technologies. Conclusions: This research illustrates the significant role of AI in revolutionizing business processes and academic practices. AI chat assistants and AI-assisted peer review methodologies represent pivotal advancements in their respective fields. The study underscores the need for continuous evaluation of the ethical implications of AI technologies to ensure their responsible and equitable use.